Costs and trends in the usage of biological therapy for rheumatoid arthritis - a retrospective study (2018)
Objectives: The aim of this study was to identify the risk of depression and assess the relationship between comorbid depression, healthcare utilization and healthcare expenditures in patients with rheumatoid arthritis (RA). Methods: We used 2015 Medical Expenditure Panel Survey (MEPS) to identify patients with RA and depression. The risk of being depressed was estimated using multiple logistic regression with survey weights. Generalized linear regression was employed to evaluate whether depression is statistically significantly associated with increased utilization and cost for office-based provider care, hospital outpatient care, hospital inpatient care, emergency room care and prescription medications. The results were adjusted for age, sex, race, marital status, education, health insurance, metropolitan area status, region, income level, and comorbidities. Results: A total number of 6,290 RA patients were identified from 2015 MEPS data set, representing a population size of 244,515,143. Of all the RA patients in 2015, 1,163 were found to have medical records of comorbid depression. Patients with RA were 2.1 times more likely to be depressed after adjusting for confounding variables (95%CI 1.80-2.42). Depressed patients had more office-based visits (p emergency room visits (p=0.0136), hospital admissions (p=0.0330), filled more prescriptions (p spent more on outpatient care (p=0.001), prescription medications (p=0.0003) compared to their counterparts. The difference in total health care cost per person was around $4,000. Conclusions: RA is associated with an increased cost and utilization of health care. Collaborative care might be indicated for future cost savings